First Look at the Venoms of Two Sinomicrurus Snakes: Differences in Yield, Proteomic Profiles, and Immunorecognition by Commercial Antivenoms - Xiang-Yu Li; Ya-Qi Zhang; Xin-Ru Qian; Hong-Yan Zhao; Hong-Liang Lu; Jian-Fang Gao (Toxins)
Chinese coral snakes (Sinomicrurus) are highly neglected regarding their venom profiles and harm to humans, which impedes our ability to deeply understand their biological properties and explore their medicinal potential. In this study, we performed a comparative analysis to reveal the venom profiles of two Chinese coral snakes in terms of their venom yields, proteomic profiles, and immunorecognition by commercial antivenoms. The results showed that Sinomicrurus kelloggi expels more venom (lyophilized venom mass) than Sinomicrurus maccelellandi but possesses a similar solid venom content. These interspecific differences in venom yield were influenced by the snout–vent length. The venoms of these two species varied in their electrophoretic profiles, as well as in the presence or absence and relative abundance of protein families. They exhibited a 3-FTx-predominant phenotype, where the S. maccelellandi venom was dominated by 3-FTx (32.43%), SVMP (23.63%), PLA2 (19.88%), and SVSP (12.61%), while the S. kelloggi venom was dominated by 3-FTx (65.81%), LAAO (11.35%), and AMP (10.09%). While both the commercial Naja atra and Bungarus multicinctus antivenoms could immunorecognize these two Chinese coral snake venoms, the N. atra antivenom possessed a higher neutralization capability than the B. multicinctus antivenom for both species of coral snakes. Our findings show significant interspecific variations in the venom profiles of these Sinomicrurus snakes for the first time. We suggest screening or preparing specific antivenoms with high efficiency for the clinical treatment of envenomation caused by these snakes.